Digital technologies, artificial intelligence, and bureaucratic transformation. (February 2022) - Newman, Joshua; Mintrom, Michael; O'Neill, Deirdre
Highlights: Obstruction and expense are two core qualities of bureaucracy. Upcoming advances in technology could make bureaucracy more efficient than ever. Bureaucracy is not disappearing. There is a paradox here. Bureaucracy is not being threatened by new computing technologies, it is being enabled. Public agencies should embrace advanced computing and look for ways for it to further public service objectives. Abstract: Bureaucracies are often criticized for their inflexibility, budget-maximizing wastefulness, and excessive rules and procedures. Rapid advances in technology, including the expansion of digital government, the use of artificial intelligence, and the ability to collect and analyze big data, promise to make public sector organizations leaner, more efficient, and more responsive to citizens' needs. While these technological changes have prompted some observers to forecast the end of bureaucracy, data from many countries show that bureaucratic public organizations are not disappearing. In this article, we argue that this paradox can be explained by revisiting some of the foundational work of sociologist Max Weber, who envisioned public administration itself as a bureaucratic machine. Advanced computing technologies, like artificial intelligence, are reinforcing bureaucratic tendencies in the public sector, not eliminating them. While advances in technology may transform the way public sector organizations operate, they can also serve to strengthen bureaucracy's core purpose.